Optimal uterotonic management. Issue 1 (May 2022) - Heesen, Michael; Orbach-Zinger, Sharon
Abstract : Uterotonics play an important role in the management of postpartum haemorrhage (PPH), often caused by uterine atony. The World Health Organization (WHO) recommends the application of uterotonics for all births. Oxytocin, considered the first-line uterotonic, binds to a G protein-coupled receptor which is subject to down sensitization upon repeated or prolonged administration of oxytocin. Consequently, a uterotonic with a different mechanism of action should be chosen early when oxytocin does not restore uterine tone. Choice of the second-line uterotonic is determined by institutional preferences as well as by maternal co-morbidities since most uterotonics have cardiovascular side effects. Slow injection of all uterotonics is strongly recommended to blunt these reactions. Methylergometrine and carboprost should, therefore, be avoided in many cardiovascular pathologies. Carbetocin is a chemical modification of oxytocin with a longer half-time, and therefore one bolus of carbetocin is usually sufficient. Its heat stability makes it an ideal candidate in resource-restricted settings.